Psychedelics and critical theory: A response to Hauskeller's individualization and alienation in psychedelic psychotherapy - Tempone-Wiltshire, Julien; Dowie, Tra-ill (Journal of psychedelic studies, 2023)
In the monograph Philosophy and Psychedelics: Frameworks for Exceptional Experience, Hauskeller raises the important subject of individualization and alienation in psychedelic psychotherapy. Under the prevailing conditions of neoliberalism, Hauskeller contends that psychedelic-assisted psychotherapy appropriates Indigenous knowledges in an oppressive fashion, may be instrumentalised to the ends of productivity gain and symptom suppression, and may be utilised to mask societal systems of alienation. Whilst offering a valuable socio-political critique of psychedelics' clinical uptake, we suggest that Hauskeller's view does not adequately acknowledge the ways in which psychedelics offer a challenge to the Western reductive bio-medical understanding of healing and wellbeing. It is contended herein that Indigenous knowledges, in alliance with a range of emerging sciences, offer both an engagement with ethnomedicines in a less harmfully appropriative fashion, and a renewed understanding of the means by which psychedelics achieve therapeutic change. With this understanding, what becomes apparent are the potential ways in which psychedelic medical usage may produce positive feedback upon the oppressive systems in which we are embedded. That is, transpersonal experience through encounters with the ineffable may offer a revisioning of Western psychology and cognitive science. Indeed, if psychedelics are approached with an understanding of the actual means by which they produce therapeutic outcomes—changing mental representations of the self, or self-insight derived through non-ordinary states of consciousness—then psychedelic psychotherapy offers a reimagining of psychiatric nosology, challenging conventional understandings of both pathology and wellbeing through an overturning of specified and discrete deficit models of psychopathology. This may provide both a critique of the prevailing categories used to describe madness and an expansion of our understanding of the mind-body relation, as well as an increased recognition of positive psychology grounded in cross-cultural contemplative traditions. This provides an implicit challenge to the pharmaceutical industrial-complex and its profit motives; and the corresponding neoliberalist, globalising tendencies which Hauskeller seeks to address.